New species and notes on Chinese species of the genus Misolampidius (Coleoptera: Tenebrionidae: Cnodalonini) - Jiang, Ri-Xin; Hou, Jia-Lin; Wang, Shuo (Zootaxa, 2020)
A new species of the genus Misolampidius Solsky, 1875, Misolampidius qiaoweipengi sp. nov. from Henan, China, is described. In addition, supplementary descriptions for Misolampidius tentyrioides Solsky, 1876, M. qianshanensis Li, 1992 and M. satoi Masumoto, Akita & Utsunomiya, 2003 are provided.